Robustness of Optical Response for Self‐Assembled Plasmonic Metamaterials with Morphological Disorder and Surface Roughness. Issue 8 (17th February 2020) - Shen, Nian‐Hai; Hossen, Md Mir; Hillier, Andrew C.; Koschny, Thomas; Soukoulis, Costas M.
Abstract: Bottom‐up fabrication of metallized biotemplated nanostructures to form specific plasmonic nanoresonators holds promise as a means of achieving large‐scale optical metamaterials. However, in contrast to top‐down methods, the stochastic growth of self‐assembled nanoresonators is prone to significant disorder and surface roughness, which naturally raise an important question about the robustness of their resonant properties in terms of structural imperfections. An aggregated‐random‐sphere model is developed to mimic the nucleated growth of metallized DNA origami assembly, leading to meta‐atoms with realistic, experimentally observed morphological disorder and surface roughness. Using the well‐known split‐ring‐resonator (SRR) motif as an example, the resonant properties of meta‐atoms under different levels of roughness are investigated and a strong tolerance of optical response against morphological disorder is revealed. It is found that in SRRs, even with dramatic roughness introduced, the expected resonances are still observed, despite broadening line shapes compared to ideal smooth structure. Only for extreme disorder, which causes drastic segmentation of SRRs, does the resonant response disappear. The demonstrations are very encouraging for the prospects of bottom‐up fabrication toward versatile functional metamaterials and metadevices. Abstract : Metallized biotemplated nanostructures promise to enable large‐scale optical metamaterials. Their stochastic growth, however, leads to significant disorder. The nucleated growth of metallized DNA is modeled to simulate split‐ring resonators (SRRs) with realistic, experimentally observed morphological disorder and surface roughness. A surprisingly robust response of the corresponding resonant metasurface is found that only disappears for extreme disorder that causes segmentation of the SRRs.